Facilities and difficulties observed by nurses in assisting families - Sonia Silva Marcon; Mislaine Casagrande de Lima Lopes; Mariana Bovo Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The present descriptive study, of a qualitative nature, had as objective to investigate the facilities and difficulties faced by Basic Care professionals when working with families. Data was collected from September to December of 2006, from 11 nurses working in nine basic care units in the city of Maringá, Paraná State, Brazil, using semi-structured interviews. The results showed that, although all nurses consider family assistance to be important, only slightly more than half (54.5%) feel prepared to work with families. Of those who do not feel prepared, most attribute it to the lack of specific training, as this theme is not approached during professional training and refresher programs, or is done only in a superficial manner. The home visit is considered to be the main tool to the fulfillment of this care, which is currently still too focused on the sick person. The main facilitating factor in this assistance is the bond between the nurse and the families, and the main difficulties are: the large number of visits to be made by the nurse, the distance between the care unit and the coverage area (associated with a lack of motor vehicles for transportation to these families' homes), and incomplete teams. It was concluded that the city must invest more in the training of nurses and other members of the Family Services team, as well as in the structuring of service, in order to promote the creation of a professional/patient bond - which is fundamental when working with families.